Three-dimensional self-assembled porous carbon-based electromagnetic shielding material and preparation method thereof, self-supporting porous carbon-based film and preparation method thereof, electromagnetic shielding material, electronic device, chip and electronic equipment
Patent Information
- Application Number
- CN202611401225.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-09-10
- Publication Date
- 2026-10-16
AI Technical Summary
[0006]然而,纯碳基电磁屏蔽材料在实际应用中也面临着一系列挑战
[0034] In a seventh aspect, this disclosure provides a chip comprising the three-dimensional self-assembled porous carbon-based electromagnetic shielding material described in any one of the first aspects, or comprising the self-supporting porous carbon-based thin film described in the fourth aspect.
Smart Images

Figure CN122934765A_ABST
Abstract
Description
Technical Field
[0001] This disclosure relates to the field of electromagnetic shielding materials technology, specifically to a three-dimensional self-assembled porous carbon-based electromagnetic shielding material and its preparation method, a self-supporting porous carbon-based thin film and its preparation method, electromagnetic shielding materials, electronic devices, chips, and electronic equipment. Background Technology
[0002] In the application of various magnetic field-sensitive devices, electromagnetic interference has always been a key factor affecting measurement accuracy. Current sensors, such as Hall effect sensors, giant magnetoresistive sensors, and tunneling magnetoresistive sensors, are easily affected by surrounding electromagnetic fields during operation, leading to deviations or noise in the measurement signal, which in turn affects the sensor's detection sensitivity and stability. Integrating a high-performance electromagnetic shielding layer around the sensor chip is an effective means to prevent external stray magnetic field interference and ensure the accuracy and reliability of the measurement signal.
[0003] Currently, the most widely used electromagnetic shielding solution in industry uses highly conductive metals such as silver, copper, and aluminum as the shielding body. These materials utilize the induced current and reverse magnetic field generated by internal free electrons under the influence of an electromagnetic field to reflect and attenuate electromagnetic waves. Through processes such as electroplating, sputtering, coating, and stamping, a shielding layer is formed on the surface of the device. Metal shielding materials, due to their high conductivity, achieve good shielding effects and are currently the most mature and widely used electromagnetic protection method.
[0004] However, traditional metallic shielding materials still have many limitations in practical applications. First, the high density of metals hinders the miniaturization and lightweighting of electronic devices. Second, metals are susceptible to corrosion, making it difficult to guarantee long-term reliability in complex environments. Furthermore, the processing and shaping of metals is difficult, limiting their application in irregularly shaped or flexible devices. More importantly, metallic shielding relies primarily on reflection, leading to secondary electromagnetic wave reflection and pollution. Simultaneously, achieving high shielding effectiveness (e.g., greater than 60 dB) using metallic solutions often requires significant costs, limiting their widespread practical application.
[0005] In response to the aforementioned shortcomings of metallic shielding materials, pure carbon-based dielectric loss electromagnetic shielding materials, with carbon materials such as carbon fiber, carbon nanotubes, graphene, and mesoporous carbon as their core, have received widespread attention in recent years. Carbon-based materials have advantages such as low density, corrosion resistance, large specific surface area, and excellent dielectric properties. They are applied to the protection of electronic devices through coatings, composites, and self-supporting thin films, aiming to replace traditional metallic shields and solve problems such as the heavy weight, easy corrosion, difficult processing and forming, and secondary reflection pollution of metallic materials.
[0006] However, pure carbon-based electromagnetic shielding materials also face a series of challenges in practical applications. First, carbon materials have high conductivity, which easily leads to skin effect and impedance mismatch. The input impedance of the material differs significantly from its free-space impedance (approximately 377Ω), affecting the effective entry of incident electromagnetic waves into the material's interior, causing a large amount of electromagnetic waves to be reflected at the material surface. Second, the loss mechanism of pure carbon materials is relatively simple, mainly relying on dielectric loss, making it difficult to simultaneously achieve strong reflection loss and a wide effective absorption frequency band, failing to meet the requirements of electromagnetic shielding technology for electrode materials. Furthermore, the limited dispersion of carbon-based conductive fillers (such as carbon nanotubes and graphene) in polymer matrices hinders their interaction with the matrix, negatively impacting electromagnetic shielding effectiveness. The complex synthesis methods and high preparation costs of some carbon materials also impede their large-scale application to some extent.
[0007] In summary, how to fully leverage the advantages of carbon materials, such as their lightweight and corrosion resistance, while overcoming their skin effect and impedance mismatch problems and enriching their loss mechanisms, thereby improving electromagnetic shielding effectiveness and enabling carbon-based materials to be more widely used in electromagnetic shielding technology, has become an urgent technical problem to be solved in this field. Summary of the Invention
[0008] To address the problems in related technologies, this disclosure provides a three-dimensional self-assembled porous carbon-based electromagnetic shielding material and its preparation method, a self-supporting porous carbon-based thin film and its preparation method, electromagnetic shielding materials, electronic devices, chips, and electronic devices.
[0009] In a first aspect, this disclosure provides a three-dimensional self-assembled porous carbon-based electromagnetic shielding material, the three-dimensional self-assembled porous carbon-based electromagnetic shielding material comprising: a three-dimensional porous carbon-based sponge; wherein: The three-dimensional porous carbon-based sponge has a three-dimensional flower-like structure, which is formed by multiple two-dimensional nanosheets contained in the three-dimensional porous carbon-based sponge through self-assembly and interlacing. The surface of the two-dimensional nanosheet has a rough morphology and a composite sheet structure. The composite sheet structure is formed by the self-assembly of magnetic nanoparticles connected by a porous carbon framework. The magnetic nanoparticles are embedded or anchored to the surface and interior of the porous carbon framework. The three-dimensional porous carbon-based sponge contains a hierarchical pore structure, which is formed by interconnected mesopores and macropores. The gaps between the multiple two-dimensional nanosheets constitute the macropores, and the mesopores are distributed inside and on the surface of the two-dimensional nanosheets. The large aperture is used to scatter and reflect the incident electromagnetic wave multiple times to enhance scattering loss and reflection loss; the meso aperture is used to extend the propagation path of the incident electromagnetic wave to enhance ohmic loss and dielectric loss.
[0010] According to embodiments of this disclosure, the three-dimensional porous carbon-based sponge is further doped with heteroatoms; the heteroatoms are covalently doped into the lattice interior and surface of the porous carbon framework.
[0011] According to embodiments of this disclosure, wherein: The heteroatoms include non-metallic elements, including one or more of nitrogen, fluorine, phosphorus, and sulfur; the heteroatoms exist in the three-dimensional porous carbon-based sponge in the form of single-element doping or multiple-element co-doping.
[0012] According to embodiments of this disclosure, the heteroatoms account for 1 wt% to 5 wt% of the mass percentage in the three-dimensional porous carbon-based sponge.
[0013] According to embodiments of this disclosure, the specific surface area of the three-dimensional porous carbon-based sponge is 400 m². 2 g -1 ~800 m 2 g -1 .
[0014] According to embodiments of this disclosure, the magnetic nanoparticles include one or more of iron, cobalt, and nickel, and the particle size of the magnetic nanoparticles is 5 nm to 10 nm.
[0015] According to embodiments of this disclosure, the diameter of the mesopores is in the range of 2 nm to 50 nm, the diameter of the macropores is in the range of 50 nm to 120 nm, the thickness of the two-dimensional nanosheets is 30 nm to 80 nm, and the aspect ratio is 20 to 100; the diameter of a single flower unit of the three-dimensional flower structure is 8 μm to 12 μm.
[0016] In a second aspect, this disclosure provides a method for preparing the three-dimensional self-assembled porous carbon-based electromagnetic shielding material according to any one of the first aspects, the method comprising: Magnetic metal-based MOF materials are generated based on magnetic metal salts and organic ligands; Magnetic metal-based MOFs sponges are generated based on the aforementioned magnetic metal-based MOFs materials and alkali metal additives; The magnetic metal-based MOFs sponge was subjected to pyrolysis treatment to obtain a three-dimensional porous carbon-based sponge. The three-dimensional porous carbon-based sponge constitutes the three-dimensional self-assembled porous carbon-based electromagnetic shielding material.
[0017] According to embodiments of this disclosure, the generation of magnetic metal-based MOFs materials based on magnetic metal salts and organic ligands includes: The magnetic metal salt and the organic ligand are dispersed in a solvent, ultrasonicated and stirred to obtain a first mixed solution; the first mixed solution is then heated to obtain the magnetic metal-based MOF material. The process of generating magnetic metal-based MOF sponges based on the magnetic metal-based MOFs material and alkali metal additives includes: The magnetic metal-based MOFs material and the alkali metal additive are dispersed in a solvent to obtain a second mixed solution; the second mixed solution is freeze-dried to obtain the magnetic metal-based MOFs sponge.
[0018] According to embodiments of this disclosure, the solvent comprises anhydrous ethanol and deionized water; the volume ratio of anhydrous ethanol to deionized water is 3:1 to 5:1; and the temperature range of the heating reaction is... The duration of the heating reaction is The temperature range for freeze-drying is: The freeze-drying time range is .
[0019] According to an embodiment of this disclosure, the heating reaction of the first mixed solution includes: first transferring the first mixed solution to a polytetrafluoroethylene reaction flask and then heating the first mixed solution to react. The freeze-drying of the second mixed solution includes: first transferring the second mixed solution into a polytetrafluoroethylene reaction flask and then freeze-drying the second mixed solution.
[0020] According to an embodiment of this disclosure, the pyrolysis treatment includes: heating the magnetic metal-based MOF sponge to an annealing temperature under a protective atmosphere, annealing for a preset time, and then cooling to room temperature.
[0021] According to embodiments of this disclosure, the protective atmosphere includes an argon atmosphere; the annealing temperature is... The preset annealing time is The heating rate is .
[0022] According to embodiments of this disclosure, the mass ratio of the alkali metal additive to the magnetic metal-based MOF material is 2:1 to 4:1.
[0023] According to embodiments of this disclosure, the magnetic metal salt includes one or more of cobalt nitrate, iron nitrate, and nickel nitrate; the organic ligand includes dipotassium salt of 2,6-naphthalenedicarboxylate.
[0024] According to embodiments of this disclosure, the alkali metal auxiliaries include one or more of metal chlorides, metal sulfates, metal carbonates, and metal bicarbonates, wherein the metal chlorides include sodium chloride and / or potassium chloride; the metal sulfates include sodium sulfate and / or potassium sulfate; the metal carbonates include sodium carbonate and / or potassium carbonate; and the metal bicarbonates include sodium bicarbonate and / or potassium bicarbonate.
[0025] According to embodiments of this disclosure, before pyrolyzing the magnetic metal-based MOFs sponge, the preparation method further includes: mixing the magnetic metal-based MOFs sponge with a heteroatom source to dope the three-dimensional porous carbon-based sponge with heteroatoms.
[0026] According to embodiments of this disclosure, the pyrolysis treatment of the mixed materials includes: The mixed material is heated to the annealing temperature under a protective atmosphere, annealed for a preset time, and then cooled to room temperature to form a non-metallic doped three-dimensional porous carbon-based sponge.
[0027] According to embodiments of this disclosure, the heteroatom source includes: a non-metallic dopant source; the non-metallic dopant source in the heteroatom source includes one or more of urea, ammonium fluoride, sodium hypophosphite, and sulfur; the mass ratio of the non-metallic dopant source to the magnetic metal-based MOF sponge is 10:1 to 20:1; the protective atmosphere includes: an argon atmosphere; the annealing temperature is... The preset annealing time is The heating rate is .
[0028] Thirdly, this disclosure provides a method for preparing a self-supporting porous carbon-based thin film, the method comprising: The three-dimensional self-assembled porous carbon-based electromagnetic shielding material described in any one of the first aspects is dispersed in water with a polymer adhesive at a preset mass ratio to obtain a mixed slurry. The mixed slurry is vacuum filtered to form a thin film, and the film is dried to obtain a self-supporting porous carbon-based thin film.
[0029] According to embodiments of this disclosure, wherein: The polymer adhesive includes: polyvinyl alcohol; The preset mass ratio is ; The drying process is constant-temperature vacuum drying, with a drying temperature of [temperature value missing]. The drying time is ; The thickness of the self-supporting porous carbon-based thin film is .
[0030] According to embodiments of this disclosure, the drying temperature includes: The drying time includes: .
[0031] Fourthly, this disclosure provides a self-supporting porous carbon-based thin film, which is prepared according to any of the preparation methods described in the third aspect.
[0032] Fifthly, this disclosure provides an electromagnetic shielding material, including the three-dimensional self-assembled porous carbon-based electromagnetic shielding material described in any one of the first aspects, or including the self-supporting porous carbon-based thin film described in the fourth aspect.
[0033] In a sixth aspect, an electronic device is provided in the embodiments of this disclosure, comprising the three-dimensional self-assembled porous carbon-based electromagnetic shielding material as described in any one of the first aspects, or comprising the self-supporting porous carbon-based thin film as described in the fourth aspect.
[0034] In a seventh aspect, this disclosure provides a chip comprising the three-dimensional self-assembled porous carbon-based electromagnetic shielding material described in any one of the first aspects, or comprising the self-supporting porous carbon-based thin film described in the fourth aspect.
[0035] Eighthly, this disclosure provides an electronic device including the chip described in the seventh aspect.
[0036] According to the technical solution provided in this disclosure, efficient electromagnetic shielding is achieved by constructing a three-dimensional porous carbon-based sponge with synergistic effects of multi-level structural units and multi-level pores. This material uses two-dimensional nanosheets as the basic structural unit. Each nanosheet is a composite sheet structure, formed by a porous carbon framework connecting magnetic nanoparticles through in-situ self-assembly. The magnetic nanoparticles are embedded or anchored on the surface and interior of the carbon framework, resulting in a rough surface morphology for the nanosheets, exhibiting both dielectric and magnetic loss capabilities. Multiple two-dimensional nanosheets are further stacked and interleaved through self-assembly to form a macroscopic three-dimensional flower-like structure. This structure not only provides structural support but also creates numerous gaps between the nanosheets, forming macropores. Simultaneously, mesopores are distributed within and on the surface of the nanosheets, thus forming a multi-level porous structure with interconnected mesopores and macropores. In this multi-level pore structure, large pores are used to scatter and reflect incident electromagnetic waves multiple times to enhance scattering and reflection losses, while mesopores are used to extend the propagation path of electromagnetic waves to enhance ohmic and dielectric losses. The two types of pores work together to effectively overcome the problem that electromagnetic waves are difficult to penetrate into the interior of traditional carbon-based materials due to the skin effect and impedance mismatch. At the same time, multiple reflection losses and wide-band dielectric losses are achieved through the synergistic superposition of magnetic and dielectric losses, which significantly enhances the electromagnetic shielding effectiveness of the material.
[0037] It should be understood that the above general description and the following detailed description are exemplary and explanatory only, and are not intended to limit this disclosure. Attached Figure Description
[0038] Other features, objects, and advantages of this disclosure will become more apparent from the following detailed description of non-limiting embodiments, taken in conjunction with the accompanying drawings. In the drawings: Figure 1 This shows a scanning electron microscope image of a three-dimensional porous Co@C sponge according to an embodiment of the present disclosure; Figure 2 A flowchart illustrating a method for preparing a three-dimensional self-assembled porous carbon-based electromagnetic shielding material according to an embodiment of the present disclosure is shown. Figure 3 A flowchart illustrating another method for preparing a three-dimensional self-assembled porous carbon-based electromagnetic shielding material according to an embodiment of the present disclosure is shown. Figure 4 A flowchart illustrating a method for preparing a self-supporting porous carbon-based thin film according to an embodiment of the present disclosure is shown. Figure 5 Show Figure 1 Pore size distribution curve of three-dimensional porous Co@C sponge; Figure 6 Show Figure 1 Three-dimensional porous Co@C sponge Adsorption-desorption isotherms; Figure 7 Show Figure 1 X-ray diffraction pattern of a three-dimensional porous Co@C sponge. Detailed Implementation
[0039] In the following, exemplary embodiments of the present disclosure will be described in detail with reference to the accompanying drawings to enable those skilled in the art to readily implement them. Furthermore, for clarity, portions unrelated to the description of exemplary embodiments have been omitted from the drawings.
[0040] In this disclosure, it should be understood that terms such as “comprising” or “having” are intended to indicate the presence of features, figures, steps, behaviors, components, parts or combinations thereof disclosed in this specification, and are not intended to exclude the possibility of the presence or addition of one or more other features, figures, steps, behaviors, components, parts or combinations thereof.
[0041] It should also be noted that, unless otherwise specified, the embodiments and features described in this disclosure can be combined with each other. This disclosure will now be described in detail with reference to the accompanying drawings and embodiments.
[0042] As mentioned earlier, existing technologies mainly employ two types of electromagnetic shielding schemes. One type is traditional metal shielding, primarily using highly conductive metals such as silver, copper, and aluminum. This method achieves electromagnetic wave reflection and attenuation through the interaction of free electrons with the electromagnetic field, generating induced current and a reverse magnetic field. While this scheme is the most mature and widely used electromagnetic protection method in industry, it suffers from problems such as high density, susceptibility to corrosion, difficulty in processing and molding, and secondary reflection pollution. Furthermore, achieving high shielding effectiveness requires significant costs. The other type is pure carbon-based dielectric loss shielding materials, with carbon materials such as carbon fibers, carbon nanotubes, and graphene as their core. These materials aim to replace metals to address the aforementioned shortcomings. However, the skin effect and impedance mismatch caused by the high conductivity of these materials limit the effective entry of incident electromagnetic waves. In addition, the single dielectric loss mechanism cannot simultaneously achieve multiple reflection losses and broadband dielectric losses, failing to fully meet the material performance requirements of electromagnetic shielding technology.
[0043] To effectively overcome the skin effect and impedance mismatch problems of carbon materials while retaining their inherent advantages such as lightweight and corrosion resistance, and to achieve synergistic enhancement of multiple loss mechanisms, this disclosure proposes a technical solution starting from the microstructure design of carbon-based materials. This solution uses two-dimensional nanosheets as the basic structural unit and further self-assembles them to construct a three-dimensional porous carbon-based sponge. Specifically, this solution uses a porous carbon framework to connect magnetic nanoparticles to form a composite layered structure of two-dimensional nanosheets. Then, through self-assembly, multiple nanosheets are stacked in an interlaced manner to form a porous carbon-based sponge with a three-dimensional flower-like structure, thereby constructing a multi-level porous structure with interconnected mesopores and macropores within the material. Based on this structural design, pores of different sizes respectively play targeted electromagnetic wave loss functions such as multiple scattering and reflection, and extending the electromagnetic wave propagation path. Simultaneously, the introduced magnetic nanoparticles provide an additional magnetic loss mechanism, forming a synergistic effect with the dielectric loss of the carbon-based material, thereby effectively alleviating the impedance mismatch problem and allowing more electromagnetic waves to enter the material and be fully dissipated. This solves the problems of electromagnetic waves being unable to effectively enter and the single loss mechanism caused by the skin effect and impedance mismatch of pure carbon-based materials, thus improving the applicability and overall shielding effectiveness of carbon-based materials in the field of electromagnetic shielding.
[0044] This disclosure provides a three-dimensional self-assembled porous carbon-based electromagnetic shielding material.
[0045] In this embodiment, the three-dimensional self-assembled porous carbon-based electromagnetic shielding material comprises a three-dimensional porous carbon-based sponge. The inventors of this disclosure have discovered that by constructing carbon-based materials into a three-dimensional porous structure with synergistic effects of multi-level structural units and multi-level pores, the problem of electromagnetic waves being unable to penetrate the interior of traditional carbon-based materials due to the skin effect and impedance mismatch can be effectively overcome, while simultaneously achieving synergistic enhancement of multiple loss mechanisms.
[0046] Specifically, the three-dimensional porous carbon-based sponge possesses a three-dimensional flower-like structure, which is formed by the self-assembly and interlocking stacking of multiple two-dimensional nanosheets contained within the three-dimensional porous carbon-based sponge. The three-dimensional flower-like structure formed by the self-assembly of multiple two-dimensional nanosheets not only provides stable macroscopic scaffold support but also creates numerous open gaps between the nanosheets, laying the foundation for the subsequent construction of hierarchical porous structures. Here, self-assembly refers to the process by which basic structural units (such as nanosheets, nanoparticles, molecules, etc.) spontaneously organize and arrange themselves into thermodynamically stable aggregates with specific regular structures through non-covalent interactions (such as hydrogen bonds, van der Waals forces, electrostatic interactions, etc.) within the system, without external directional intervention.
[0047] Furthermore, each of the two-dimensional nanosheets is a composite layered structure. The two-dimensional nanosheets are formed by in-situ self-assembly of magnetic nanoparticles connected to a porous carbon framework. Specifically, this composite layered structure is formed during pyrolysis by carbonizing organic ligands to form a porous carbon framework, followed by in-situ reduction of magnetic metal ions into magnetic nanoparticles that are embedded or anchored on the surface and interior of the porous carbon framework. The porous carbon framework connects the magnetic nanoparticles, resulting in a rough surface morphology for the two-dimensional nanosheets. This composite layered structure allows the two-dimensional nanosheets to simultaneously possess the dielectric loss capability of carbon-based materials and the magnetic loss capability of magnetic nanoparticles, providing a structural basis for the synergistic effect of multiple loss mechanisms. In some embodiments, the magnetic nanoparticles include one or more of iron (Fe), cobalt (Co), and nickel (Ni), and the particle size of the magnetic nanoparticles is 5 nm to 10 nm. These magnetic nanoparticles provide a magnetic loss mechanism, which synergizes with the dielectric loss of the carbon-based materials to enhance the overall electromagnetic shielding effectiveness.
[0048] Furthermore, the three-dimensional porous carbon-based sponge comprises a hierarchical porous structure, which is formed by interconnected mesopores and macropores. Specifically, the gaps between the multiple two-dimensional nanosheets constitute the macropores, and the mesopores are distributed inside and on the surface of the two-dimensional nanosheets. Electromagnetic waves enter through the macropores and are refracted multiple times by the mesopores. This hierarchical porous structure, with its coordinated distribution of mesopores and macropores, enables the three-dimensional porous carbon sponge to possess both high reflection loss and dielectric loss capabilities, effectively extending the propagation path of electromagnetic waves and enhancing multiple scattering, thereby achieving efficient electromagnetic wave attenuation.
[0049] In one implementation of this disclosure, the three-dimensional porous carbon-based sponge is a three-dimensional porous Co@C sponge. Figure 1 A scanning electron microscope (SEM) image of a three-dimensional porous Co@C sponge according to an embodiment of the present disclosure is shown. Figure 1As shown, the three-dimensional porous Co@C sponge is a three-dimensional flower-like multi-layered porous structure formed by the self-assembly of two-dimensional nanosheets, and the two-dimensional nanosheets are formed by the self-assembly of magnetic nanoparticles connected by a porous carbon skeleton to form a rough-surfaced sheet structure.
[0050] In some embodiments of this disclosure, the diameter of the mesopore is in the range of 2 nm to 50 nm, and the diameter of the macropore is in the range of 50 nm to 120 nm. In this disclosure, the symbol “~” is used to indicate a numerical range, which includes the endpoint values before and after the “~”, for example, “50 nm to 120 nm” refers to the range of 50 nm to 120 nm.
[0051] Through the synergistic effect of the multi-level pore structure, pores of different sizes each perform their specific electromagnetic wave loss functions. Specifically, the large pores are used to scatter and reflect the incident electromagnetic waves multiple times, thereby enhancing scattering and reflection losses; the mesopores are used to extend the propagation path of the incident electromagnetic waves, thereby enhancing ohmic and dielectric losses. Through the synergistic cooperation of these two types of pores, the synergistic effect of the large pore scattering / reflection loss and the mesopore propagation path extension loss is achieved, significantly improving the overall electromagnetic shielding effectiveness of the material.
[0052] In this embodiment, the specific surface area of the three-dimensional porous carbon-based sponge is 400 m². 2 g -1 ~800 m 2 g -1 A higher specific surface area can generate more polarization sites, enhancing the absorption capacity of electromagnetic waves.
[0053] In some embodiments of this disclosure, the three-dimensional porous carbon-based sponge is further doped with heteroatoms, and the doping is uniform. The heteroatoms are covalently bonded to the interior and surface of the porous carbon framework. The introduction of heteroatoms can further increase the structural defects and polarization sites of the carbon framework, enhance dipole polarization and interfacial polarization effects, thereby further improving electromagnetic wave absorption loss. Simultaneously, heteroatom doping can further alleviate impedance mismatch, allowing more electromagnetic waves to enter the material interior, while simultaneously enhancing absorption loss and electromagnetic wave attenuation in the high-frequency band. In some embodiments, the heteroatoms include non-metallic elements, including one or more of nitrogen (N), fluorine (F), phosphorus (P), and sulfur (S). The heteroatoms exist in the three-dimensional porous carbon-based sponge in the form of single-element doping or multi-element co-doping, wherein co-doping means simultaneously introducing two or more heteroatoms into the same material (e.g., simultaneously doping with N and P, i.e., N / P co-doping). The mass percentage of the heteroatoms in the three-dimensional porous carbon-based sponge is 1 wt% to 5 wt%. By controlling the doping content of heteroatoms within the above range, it is possible to effectively regulate the electronic structure and polarization ability of the material, and improve the conductivity of carbon-based materials, thereby achieving a good balance between dielectric loss and conductivity.
[0054] In order to obtain the three-dimensional self-assembled porous carbon-based electromagnetic shielding material as described above, this disclosure also provides a method for preparing the three-dimensional self-assembled porous carbon-based electromagnetic shielding material.
[0055] Figure 2 A flowchart illustrating a method for preparing a three-dimensional self-assembled porous carbon-based electromagnetic shielding material according to an embodiment of the present disclosure is shown. Figure 2 As shown, the preparation method includes the following steps S210~S230: In step S210, magnetic metal-based MOF materials are generated based on magnetic metal salts and organic ligands.
[0056] In implementing step S210, the following method can be used: disperse the magnetic metal salt and the organic ligand in a solvent, sonicate and stir to obtain a uniform first mixed solution; heat the first mixed solution to obtain the magnetic metal-based MOF material.
[0057] In step S220, a magnetic metal-based MOF sponge is generated based on the magnetic metal-based MOF material and the alkali metal additive.
[0058] In implementing step S220, the following method can be used: disperse the magnetic metal-based MOFs material and the alkali metal additive in a solvent to obtain a uniform second mixed solution; freeze-dry the second mixed solution to obtain the magnetic metal-based MOFs sponge.
[0059] In some embodiments of this disclosure, the magnetic metal salt includes, but is not limited to, one or more of cobalt nitrate, iron nitrate, and nickel nitrate; the organic ligand includes, but is not limited to, dipotassium 2,6-naphthalenedicarboxylate, which has two carboxylate groups located at the 2 and 6 positions of the naphthalene ring, exhibiting a linearly extended coordination configuration, which is beneficial for inducing preferential growth of MOF crystals along the two-dimensional direction, thereby forming a precursor with a plate-like morphology. It is understood that the specific types of magnetic metal salts and organic ligands described above are merely illustrative examples, and those skilled in the art can select other magnetic metal salts and organic ligands capable of forming MOF structures according to actual needs; this disclosure does not impose any limitations on this.
[0060] In some embodiments of this disclosure, the mass ratio of the alkali metal additive to the magnetic metal-based MOF material is 2:1 to 4:1, more preferably 3:1; the alkali metal additive includes, but is not limited to, one or more of metal chlorides, metal sulfates, metal carbonates, and metal bicarbonates, wherein the metal chlorides include sodium chloride and / or potassium chloride; the metal sulfates include sodium sulfate and / or potassium sulfate; the metal carbonates include sodium carbonate and / or potassium carbonate; and the metal bicarbonates include sodium bicarbonate and / or potassium bicarbonate. In this disclosure, the alkali metal additive acts as a pore-forming agent during subsequent pyrolysis, activating and etching the carbon framework, which is beneficial for forming mesopores on the carbon framework, thereby increasing the specific surface area and porosity of the material.
[0061] In some embodiments of this disclosure, the solvents involved in steps S210-S220 can be anhydrous ethanol and deionized water, with a volume ratio of anhydrous ethanol to deionized water of 3:1 to 5:1, and more preferably 4:1; during the heating reaction, the temperature range of the heating reaction is... The duration of the heating reaction is During freeze-drying, the temperature range for freeze-drying is... The freeze-drying time range is .
[0062] The inventors of this disclosure have discovered through research that if the heating reaction temperature is lower than... MOFs crystals have insufficient crystallinity and low yield; if higher than This could lead to excessively rapid crystal nucleation and uneven crystal size, affecting the subsequent formation of two-dimensional nanosheets. If the freeze-drying temperature is higher than... Too rapid a solvent sublimation rate may damage the sponge structure; if it is lower than... This would increase energy consumption and raise the requirements for equipment. Therefore, controlling the parameters of the heating reaction and freeze-drying within the above range is beneficial for obtaining MOFs materials with high crystallinity and uniform morphology, as well as three-dimensional sponges with complete structures.
[0063] In some embodiments of this disclosure, when heating the first mixed solution, the first mixed solution can be transferred to a polytetrafluoroethylene (PTFE) reaction vessel before heating; similarly, when freeze-drying the second mixed solution, the second mixed solution can be transferred to a PTFE reaction vessel before freeze-drying. In this disclosure, a PTFE reaction vessel is used as the reaction container because it is resistant to high and low temperatures and has an inert surface, making it less likely to interact with the reaction system, thus effectively ensuring the purity and stability of the reaction system.
[0064] In step S230, the magnetic metal-based MOFs sponge is subjected to pyrolysis treatment to obtain a three-dimensional porous carbon-based sponge; wherein the three-dimensional porous carbon-based sponge is contained in the three-dimensional self-assembled porous carbon-based electromagnetic shielding material.
[0065] The pyrolysis treatment includes: heating the magnetic metal-based MOF sponge to an annealing temperature under a protective atmosphere, annealing for a preset time, and then cooling to room temperature to form a three-dimensional porous carbon-based sponge. The protective atmosphere includes an argon atmosphere; the annealing temperature is... The preset annealing time is The heating rate is .
[0066] The inventors of this disclosure have discovered through research that annealing temperature can affect the structure and properties of the final product. If the annealing temperature is lower than... Incomplete carbonization of organic ligands prevents the formation of a continuous porous carbon framework, and magnetic metal ions cannot be fully reduced to elemental magnetic nanoparticles; if the carbon content is higher than... This can lead to the shrinkage and collapse of the carbon framework structure, blockage of pores, and the easy aggregation and growth of magnetic nanoparticles, causing their particle size to exceed the preferred range of 5 nm to 10 nm, thus weakening the magnetic loss effect. If the heating rate is too fast (exceeding...),... During pyrolysis, the violent release of gas may damage the three-dimensional structural integrity of the sponge; if the process is too slow (below...), it may also damage the sponge's integrity. If the annealing temperature is too high, the preparation cycle will be too long, which is not conducive to industrial production. Therefore, the annealing temperature should be controlled at... The heating rate is controlled at This approach helps maintain the integrity of the three-dimensional porous structure and the nanoscale distribution of the magnetic nanoparticles while ensuring complete carbonization and full reduction of the magnetic particles. During pyrolysis, the organic ligands are carbonized into a porous carbon framework, and the metal ions in the magnetic metal salt are reduced in situ into magnetic nanoparticles, which are embedded or anchored on the surface and inside of the porous carbon framework.
[0067] In some embodiments, the preparation method further includes a non-metallic doping or co-doping step. Specifically, Figure 3 A flowchart illustrating another method for preparing a three-dimensional self-assembled porous carbon-based electromagnetic shielding material according to an embodiment of the present disclosure is shown. Figure 3 As shown, before the magnetic metal-based MOFs sponge undergoes pyrolysis treatment, the preparation method further includes step S221: In step S221, the magnetic metal-based MOF sponge is mixed with a heteroatom source to obtain a mixed material.
[0068] Thus, in step S230, the mixed material is subjected to pyrolysis treatment to obtain a three-dimensional porous carbon-based sponge doped with heteroatoms; wherein, the three-dimensional porous carbon-based sponge is contained in the three-dimensional self-assembled porous carbon-based electromagnetic shielding material.
[0069] The heteroatom source includes, but is not limited to, a non-metallic dopant source; the non-metallic dopant source includes one or more of urea, ammonium fluoride, sodium hypophosphite, and sulfur; the mass ratio of the non-metallic dopant source to the magnetic metal-based MOF sponge is 10:1 to 20:1. The heteroatom source (such as urea) decomposes to produce gas during pyrolysis, which helps to form more mesopores on the carbon framework, increasing the specific surface area and porosity, thereby providing more space for multiple scattering and reflection of electromagnetic waves.
[0070] According to embodiments of this disclosure, the pyrolysis treatment of the mixed materials includes: The mixed material is heated to the annealing temperature under a protective atmosphere, annealed for a preset time, and then cooled to room temperature to form a non-metallic doped three-dimensional porous carbon-based sponge.
[0071] The protective atmosphere includes, but is not limited to, argon atmosphere; the annealing temperature is... The preset annealing time is The heating rate is .
[0072] During pyrolysis, nonmetallic dopant sources decompose to generate active heteroatoms (such as nitrogen, fluorine, phosphorus, and sulfur). Taking nitrogen doping as an example (the doping mechanism for other heteroatoms is similar), during pyrolysis, heteroatom sources (such as urea) decompose at high temperatures, generating nitrogen-containing active species (such as NH3, N2, and CN).+ These nitrogen-containing reactive species react with carbon atoms on the surface of the carbon framework under high-temperature conditions, replacing some carbon atoms in the carbon lattice or inserting into defect sites in the carbon framework to form CN covalent bonds. Specifically, nitrogen atoms can be doped into the carbon framework in three main forms: pyridine nitrogen (N-6, located at the edge of the carbon layer, bonded to two carbon atoms), pyrrole nitrogen (N-5, located in a five-membered ring, bonded to two carbon atoms), and graphitic nitrogen (NQ, located inside the carbon layer, replacing carbon atoms and bonding to three carbon atoms). Nitrogen atoms in these different bonding states are all connected to the carbon framework through covalent bonds, thus stably doping into the interior and surface of the carbon framework lattice. Similarly, phosphorus atoms can form CP bonds by replacing carbon atoms, sulfur atoms can form CS bonds by inserting into the edge of the carbon framework or replacing carbon atoms, and fluorine atoms are mainly connected to carbon atoms on the surface of the carbon framework through covalent bonds. The heteroatoms are doped into the interior and surface of the porous carbon framework through covalent bonds. Furthermore, heteroatoms, through covalent bonding, can effectively modulate the electronic structure and surface chemistry of carbon materials, enhancing dipole polarization and interfacial polarization effects, thereby improving the absorption and attenuation capabilities of electromagnetic waves. Therefore, based on the chemical transformation mechanism during the aforementioned pyrolysis process, heteroatoms, in the form of covalent bonds, dope the carbon framework, forming structural defects and polarization centers in the porous carbon-based sponge, thus enhancing its attenuation capability for electromagnetic waves.
[0073] In some embodiments, the heteroatoms include non-metallic elements, which include one or more of nitrogen (N), fluorine (F), phosphorus (P), and sulfur (S). The heteroatoms exist in the three-dimensional porous carbon-based sponge in the form of single-element doping or multi-element co-doping. The non-metallic mass percentage of the non-metallic doped three-dimensional porous carbon-based sponge finally prepared in this disclosure is 1 wt%-5 wt%.
[0074] In this disclosure, the three-dimensional flower-like structure of the three-dimensional porous carbon-based sponge is formed during a heating reaction (hydrothermal or microwave), and its formation depends on the preferential growth of MOF crystals in the two-dimensional direction. Under heating conditions, magnetic metal salts undergo coordination reactions with organic ligands, preferentially growing along the two-dimensional direction to form MOF crystals with a plate-like morphology. When using dipotassium 2,6-naphthalenedicarboxylate as the organic ligand, MOF crystals with a good plate-like morphology can be obtained, which is retained during subsequent pyrolysis. Multiple plate-like units are interleaved and stacked to form a three-dimensional flower-like structure.
[0075] The mesopores and macropores in the three-dimensional porous carbon-based sponge have different formation causes. Macropores mainly originate from the cavities left after ice crystals are removed during freeze-drying, while mesopores mainly originate from the framework voids left after ligand molecules are removed from the MOF lattice during pyrolysis when organic ligands are carbonized, as well as the cracks formed during the high-temperature shrinkage of the carbon skeleton. These pores are interconnected, forming a hierarchical porous structure.
[0076] The preparation method provided in this disclosure uses magnetic metal-based MOFs as a precursor. MOF sponges are obtained through a freeze-drying process assisted by an alkali metal additive. The MOF framework is then pyrolyzed in situ to transform into a porous carbon framework, while simultaneously reducing magnetic metal ions to nano-magnetic particles. This achieves the synergistic effect of carbon framework formation, magnetic particle generation, and hierarchical porous structure construction in one step. The introduction of heteroatoms further enriches the polarization loss mechanism of the material. This preparation method requires no additional template agent, is simple in procedure, and operates under mild conditions, making it suitable for large-scale preparation and widespread application.
[0077] This disclosure also provides the application of the above-mentioned three-dimensional self-assembled porous carbon-based electromagnetic shielding material, namely, a method for preparing a self-supporting porous carbon-based thin film. The self-supporting porous carbon-based thin film can be used directly as an electromagnetic shielding material, or as a shielding layer or electrode layer in an electromagnetic shielding device.
[0078] Figure 4 A flowchart illustrating a method for preparing a self-supporting porous carbon-based thin film according to an embodiment of the present disclosure is shown. Figure 4 As shown, the preparation method includes the following steps S410~S420: In step S410, the three-dimensional self-assembled porous carbon-based electromagnetic shielding material and polymer adhesive described in this embodiment are dispersed in water at a preset mass ratio and then ultrasonically treated to achieve uniform dispersion, thereby obtaining a mixed slurry.
[0079] In step S420, the mixed slurry is vacuum filtered to form a thin film, and the thin film is dried to obtain a self-supporting porous carbon-based thin film.
[0080] In some embodiments of this disclosure, the polymer adhesive includes polyvinyl alcohol (PVA). PVA has good water solubility and film-forming properties, enabling it to effectively bond three-dimensional self-assembled porous carbon-based electromagnetic shielding materials to form a continuous, flexible, self-supporting film without affecting the material's electromagnetic shielding performance. Of course, those skilled in the art will understand that other water-soluble polymer adhesives with similar functions can also be applied to the technical solutions of this disclosure.
[0081] In some embodiments, the preset mass ratio of the three-dimensional self-assembled porous carbon-based electromagnetic shielding material to the polymer adhesive is: The three-dimensional self-assembled porous carbon-based electromagnetic shielding material accounts for 83 wt% to 94 wt% of the mass of the self-supporting porous carbon-based film. The inventors of this disclosure have found that if the proportion of carbon-based material is too high (greater than 8:0.5), the polymer adhesive is insufficient to effectively bond the carbon-based material particles, resulting in insufficient mechanical strength and brittleness of the film; if the proportion of carbon-based material is too low (less than 5:1), the proportion of inactive components in the film is too high, the content of electromagnetic shielding functional material per unit area decreases, and the shielding performance weakens. Controlling the mass ratio within... Within this range, it is beneficial to ensure a high electromagnetic shielding functional material loading while maintaining the integrity and flexibility of the thin film structure, thereby obtaining the best overall electromagnetic shielding performance.
[0082] In some embodiments, the vacuum filtration uses a PVDF (polyvinylidene fluoride) membrane as the filter medium. During the vacuum filtration process, the mixed slurry passes through the membrane under negative pressure, and the three-dimensional self-assembled porous carbon-based electromagnetic shielding material and polyvinyl alcohol are retained on the surface of the membrane, forming a uniform thin film layer.
[0083] In some embodiments, the drying is constant-temperature vacuum drying. Specifically, the drying temperature is... The drying time is In some embodiments, the drying temperature includes The drying time includes 6 hours. Using a constant-temperature vacuum drying method can prevent the film from cracking at high temperatures, while effectively removing residual moisture from the film, ensuring the film's flatness and structural density.
[0084] Under the above preparation conditions, the thickness of the obtained self-supporting porous carbon-based thin film is [value missing]. The inventors of this disclosure have discovered through research that the thickness of the thin film can affect its overall performance: if the film thickness is too large (greater than 2 mm), although the shielding effectiveness may be further improved, the flexibility of the film will decrease significantly, making it brittle and prone to cracking, which will make it difficult to meet the requirements for flexible or curved surface bonding in practical applications; if the film thickness is too small (less than 0.4 mm), the material load will be insufficient, the propagation path of electromagnetic waves inside the film will be too short, and it will be difficult to be fully attenuated and absorbed, resulting in a weakening of the shielding effectiveness. Therefore, controlling the film thickness within the range of 0.4 mm to 2 mm can balance good flexibility and excellent electromagnetic shielding performance. Tests show that when the thickness of the self-supporting porous carbon-based film is 0.4 mm, the electromagnetic shielding effectiveness in the 8.2-12.4 GHz frequency range is no less than 50 dB; when the thickness is 2 mm, the electromagnetic shielding effectiveness is no less than 80 dB. The bending radius of the self-supporting porous carbon-based film is no greater than 10 mm, and the electromagnetic shielding effectiveness retention rate is no less than 90% after 20 bends. This excellent flexibility makes it suitable for applications such as surface bonding of irregularly shaped devices and wearable / flexible electronic devices.
[0085] The method for preparing a self-supporting porous carbon-based thin film provided in this disclosure involves combining the above-mentioned three-dimensional self-assembled porous carbon-based electromagnetic shielding material with a polymer adhesive, followed by vacuum filtration to form a film. The preparation process is simple, convenient, and inexpensive. The resulting self-supporting porous carbon-based thin film has controllable thickness, good flexibility, and excellent electromagnetic shielding performance, which can meet the needs of different application scenarios for electromagnetic shielding materials.
[0086] Furthermore, the three-dimensional self-assembled porous carbon-based electromagnetic shielding material prepared in this disclosure can be used as an electromagnetic shielding electrode material. It possesses a multi-layered porous structure, high conductivity, high specific surface area, and a stable structure, which helps alleviate impedance mismatch. Simultaneously, it provides multiple reflection and scattering paths, as well as more polarization sites, achieving interfacial polarization and multiple scattering effects. This extends the propagation path of electromagnetic waves and enhances losses, thereby facilitating the absorption of more incident electromagnetic waves, increasing high-frequency absorption loss and electromagnetic wave attenuation, and significantly improving electromagnetic shielding effectiveness. Experimental results show that the three-dimensional porous carbon-based sponge prepared in this disclosure, as an electromagnetic shielding electrode material, as shown in Table 1, achieves an electromagnetic shielding effectiveness of over 54.3 dB in the frequency range of 8.2-12.4 GHz. After heteroatom doping, the shielding effectiveness can be further improved to over 62.7 dB, and the N / P co-doped sample can even reach 68.3 dB, demonstrating excellent electromagnetic shielding performance. This disclosure provides a new approach for preparing porous carbon-based electromagnetic shielding electrode materials and promotes the application of carbon-based materials in electromagnetic shielding technology.
[0087] Table 1 Electromagnetic shielding performance data of some non-metal-doped three-dimensional porous carbon-based sponges prepared by the method disclosed in this paper. sample Electromagnetic shielding performance (dB) Three-dimensional porous Co@C sponge 54.3 N-doped three-dimensional porous Co@C sponge 62.7 N,P co-doped three-dimensional porous Co@C sponge 68.3 Three-dimensional porous Ni@C sponge 52.9 The preparation method provided in this disclosure will be described in detail below with reference to specific embodiments. Specific Implementation Example 1: 1.2 mmol Co(NO3)2·6H2O and 0.8 mmol dipotassium salt of 2,6-naphthalenedicarboxylic acid were dispersed in 100 ml of a mixed solution of anhydrous ethanol and deionized water (volume ratio of anhydrous ethanol to deionized water 4:1). The mixture was ultrasonically dispersed and magnetically stirred at room temperature to obtain a homogeneous first mixed solution. The first mixed solution was then transferred to a high-pressure reactor. At a certain temperature, the reaction was heated for 24 h to obtain magnetic metal-based MOF materials, namely Co-MOFs. Subsequently, KCl and Co-MOFs were uniformly dispersed in a mixed solution of anhydrous ethanol and deionized water at a mass ratio of 2:1. At the specified temperature, the Co-MOFs sponge was freeze-dried for 48 h to obtain a Co-MOFs sponge. Subsequently, the Co-MOFs sponge was placed in a tube furnace and annealed at 500 °C for 2 h under an argon atmosphere with a heating rate of 5 °C / min to obtain a three-dimensional porous Co@C sponge, which is a three-dimensional porous carbon-based sponge, and also a three-dimensional self-assembled porous carbon-based electromagnetic shielding material.
[0089] When the three-dimensional porous Co@C sponge prepared in Specific Example 1 above is used as an electrode material, the preparation method of the three-dimensional porous Co@C sponge electrode includes: ultrasonically dispersing the prepared three-dimensional porous Co@C sponge and polyvinyl alcohol in water at a mass ratio of 8:1 to obtain a mixed slurry. The obtained mixed slurry is then vacuum filtered to form a thin film on a PVDF filter membrane. The three-dimensional porous Co@C sponge thin film electrode was obtained by drying at a constant temperature for 8 h, and the total thickness of the film was 0.5 mm.
[0090] For example Figure 1 The three-dimensional porous Co@C sponge shown has a specific surface area of 482.2 m². 2 g -1 The pore volume is 0.7 cm³. 3 g -1 The mesoporous rate is 72.3%, and the pore diameter is distributed between 2 nm and 120 nm, exhibiting a mesoporous-macroporous porous structure, mainly composed of mesopores.
[0091] Scanning electron microscopy (SEM) measurements show that the thickness of the two-dimensional nanosheets is 30 nm to 80 nm, and the aspect ratio is 20 to 100. The diameter of a single flower-like unit in the three-dimensional flower structure is 8 μm to 12 μm. The three-dimensional flower structure can be further divided into several independent micrometer-scale aggregates, each aggregate being a single flower-like unit assembled from multiple interleaved stacked two-dimensional nanosheets. These geometric parameters indicate that the three-dimensional flower structure of this disclosure has distinct microstructural characteristics. The two-dimensional nanosheets are sheet-like and have a high aspect ratio, which facilitates the interleaved stacking of the nanosheets, thereby forming a stable three-dimensional flower-like framework and abundant macropores between the sheets.
[0092] Figure 5 Show Figure 1 The diagram shows the pore size distribution curves of the three-dimensional porous Co@C sponge. Those skilled in the art will understand that the above pore size ranges are not absolute limits; due to fluctuations in preparation conditions, reasonable deviations may exist within each pore size range around the above values. Hierarchical porous structures with the above pore size distribution ranges can achieve graded loss of electromagnetic waves at different scales.
[0093] Figure 6 Show Figure 1 Three-dimensional porous Co@C sponge Adsorption-desorption isotherms. For example... Figure 6 As shown, with relative pressure As the value increased from 0 to 1.0, the adsorption capacity increased from approximately 23 cm³. 3 g -1 The monotony increases to approximately 148 cm 3 g -1 . Figure 6 The data shown is from a specific embodiment. The adsorption test results, including the amount of adsorption and the shape of the isotherm, are related to the specific preparation conditions of the material. Different embodiments may exhibit different adsorption characteristics, which should not be regarded as a limitation on the scope of protection of this disclosure.
[0094] Figure 7 Show Figure 1 X-ray diffraction pattern of a three-dimensional porous Co@C sponge. (See image.) Figure 7 As shown, the diffraction peaks of the Co@C sample are consistent with the Co diffraction peaks in the standard PDF card (PDF#15-0806), indicating that the prepared sample contains elemental Co metal, rather than oxides or other compounds of Co.
[0095] The electromagnetic shielding performance of the three-dimensional porous Co@C sponge electrode prepared using the above method was tested. The experimental method is as follows: The electromagnetic shielding performance of the prepared three-dimensional porous Co@C sponge electrode was tested using a vector network analyzer (Keysight N5247B, USA) in the 8.2–12.4 GHz frequency band. The three-dimensional porous Co@C sponge electrode exhibited excellent electromagnetic shielding performance, which fluctuated around 54.3 dB and generally showed an increasing trend with increasing frequency. Specific Implementation Example 2 0.6 mmol Co(NO3)2·6H2O and 0.4 mmol 2,6-naphthalenedicarboxylic acid dipotassium salt were dispersed in 100 ml of a mixed solution of anhydrous ethanol and deionized water (volume ratio of anhydrous ethanol to deionized water 4:1). The mixture was ultrasonically dispersed and magnetically stirred at room temperature to obtain a homogeneous first mixed solution. The first mixed solution was then transferred to a high-pressure reactor. The reaction was heated at a certain temperature for 24 hours to obtain Co-MOFs. Subsequently, K₂CO₃ and Co-MOFs were uniformly dispersed in a mixed solution of anhydrous ethanol and deionized water at a mass ratio of 3:1. At a certain temperature, the Co-MOFs sponge was freeze-dried for 48 hours to obtain the Co-MOFs sponge. Then, urea and Co-MOFs sponge were mixed evenly at a mass ratio of 10:1 and placed in a tube furnace. The mixture was annealed at 600 °C for 2 h under an argon atmosphere with a heating rate of 5 °C / min to obtain a three-dimensional porous nitrogen-doped Co@C sponge, which is a nitrogen-doped porous carbon-based sponge, and also a three-dimensional self-assembled porous carbon-based electromagnetic shielding material.
[0097] The method for preparing the three-dimensional porous Co@C sponge electrode in Specific Example 1 was adopted to prepare a nitrogen-doped three-dimensional porous Co@C sponge electrode using the nitrogen-doped three-dimensional porous Co@C sponge material obtained in this specific example. Specifically, the prepared nitrogen-doped three-dimensional porous Co@C sponge and polyvinyl alcohol were ultrasonically and uniformly dispersed in water at a mass ratio of 8:1 to obtain a mixed slurry. The obtained mixed slurry was vacuum filtered to form a thin film on a PVDF filter membrane. After drying at a constant temperature for 8 h, a nitrogen-doped three-dimensional porous Co@C sponge thin film electrode was obtained, with a total film thickness of 0.5 mm. Specific Implementation Example 3 2.4 mmol Co(NO3)2·6H2O and 1.6 mmol 2,6-naphthalenedicarboxylic acid dipotassium salt were dispersed in 100 ml of a mixed solution of anhydrous ethanol and deionized water (volume ratio of anhydrous ethanol to deionized water 3:1). The mixture was ultrasonically dispersed and magnetically stirred at room temperature to obtain a homogeneous first mixed solution. The first mixed solution was then transferred to a high-pressure reactor. The reaction was heated at a certain temperature for 24 h to obtain Co-MOFs. Subsequently, KHCO3 and Co-MOFs were uniformly dispersed in a mixed solution of anhydrous ethanol and deionized water at a mass ratio of 4:1. At a certain temperature, the Co-MOFs sponge was freeze-dried for 48 hours to obtain the Co-MOFs sponge. Then, urea, sodium hypophosphite and Co-MOFs sponge were mixed evenly at a mass ratio of 10:10:1 and placed in a tube furnace. The mixture was annealed at 600 °C for 2 h under an argon atmosphere with a heating rate of 5 °C / min to obtain a three-dimensional porous nitrogen / phosphorus co-doped Co@C sponge, which is a nitrogen / phosphorus co-doped porous carbon-based sponge, and also a three-dimensional self-assembled porous carbon-based electromagnetic shielding material.
[0099] Using the preparation method of the three-dimensional porous Co@C sponge electrode in Specific Example 1, a nitrogen / phosphorus co-doped three-dimensional porous Co@C sponge electrode was prepared using the nitrogen / phosphorus co-doped three-dimensional porous Co@C sponge material obtained in this example. Specifically, the prepared nitrogen / phosphorus co-doped three-dimensional porous Co@C sponge and polyvinyl alcohol were ultrasonically and uniformly dispersed in water at a mass ratio of 8:1 to obtain a mixed slurry. The obtained mixed slurry was vacuum filtered to form a thin film on a PVDF filter membrane. After drying at a constant temperature for 8 h, a nitrogen / phosphorus co-doped three-dimensional porous Co@C sponge thin film electrode was obtained, with a total film thickness of 0.5 mm. Specific Implementation Example 4 1.2 mmol Ni(NO3)2·6H2O and 0.8 mmol dipotassium salt of 2,6-naphthalenedicarboxylic acid were dispersed in 100 ml of a mixed solution of anhydrous ethanol and deionized water (volume ratio of anhydrous ethanol to deionized water 3:1). The mixture was ultrasonically dispersed and magnetically stirred at room temperature to obtain a homogeneous first mixed solution. The first mixed solution was then transferred to a high-pressure reactor. The reaction was heated at a certain temperature for 24 hours to obtain Ni-MOFs. Subsequently, KCl and Ni-MOFs were uniformly dispersed in a mixed solution of anhydrous ethanol and deionized water at a mass ratio of 3:1. At a certain temperature, the Ni-MOFs sponge was freeze-dried for 48 hours to obtain a Ni-MOFs sponge. Subsequently, the Ni-MOFs sponge was placed in a tube furnace and annealed at 600 °C for 2 h in an argon atmosphere with a heating rate of 5 °C / min to obtain a three-dimensional porous Ni@C sponge, which is a three-dimensional porous carbon-based sponge, and also a three-dimensional self-assembled porous carbon-based electromagnetic shielding material.
[0101] The three-dimensional porous Ni@C sponge electrode was prepared using the method described in Specific Example 1. Specifically, the prepared three-dimensional porous Ni@C sponge and polyvinyl alcohol were ultrasonically and uniformly dispersed in water at a mass ratio of 8:1 to obtain a mixed slurry. The mixed slurry was then vacuum filtered to form a thin film on a PVDF filter membrane. The three-dimensional porous Ni@C sponge thin film electrode was obtained by drying at a constant temperature for 8 h, and the total thickness of the film was 0.5 mm.
[0102] In the specific embodiments 1-4 provided above, the specific experimental conditions used in each step are as follows: the ultrasonic power for ultrasonic dispersion is 180 W, and the ultrasonic duration is 30 min; the magnetic stirring speed is 300 rpm, and the stirring time is 30 min; the pyrolysis treatment in each embodiment is carried out under an atmospheric pressure argon atmosphere; the heating program is to directly heat from room temperature to the annealing temperature at a constant rate; after annealing, the products are cooled to room temperature in the furnace. In addition, the products obtained after pyrolysis are post-treated: washed three times each with water and ethanol, and then... Dry for 12 hours.
[0103] It is understood that the specific experimental parameters mentioned above, such as ultrasonic power, ultrasonic duration, stirring speed, stirring time, pyrolysis atmosphere type, pressure conditions, heating program, cooling method, and the type of washing liquid, number of washing cycles, drying temperature, and drying time in the post-processing steps, are merely exemplary implementations of this disclosure and do not constitute a limitation on the scope of protection of this disclosure. Those skilled in the art can reasonably adjust the above parameters according to the actual types of raw materials used, equipment conditions, and target product performance requirements. As long as the experimental conditions adopted can achieve the technical solution of this disclosure and reach the expected technical effect, they should all fall within the scope of protection of this disclosure.
[0104] Furthermore, in the specific embodiments 1-4 provided above, the 8:1 mass ratio of each three-dimensional porous carbon-based sponge to polyvinyl alcohol is merely an exemplary implementation of this disclosure. Those skilled in the art can, according to actual needs, implement the methods defined in this disclosure. Adjust this ratio within the specified range.
[0105] To verify the synergistic effect of alkali metal additives, freeze drying, and low-temperature pyrolysis in this disclosure, the same Co-MOF precursor as in Specific Example 1 was used, but a comparative experiment was conducted under the following conditions: no alkali metal additive (KCl) was added, conventional vacuum drying was used instead of freeze drying, the pyrolysis temperature was increased to 700°C, and the remaining steps were consistent with Specific Example 1.
[0106] The specific steps are as follows: 1.2 mmol Co(NO3)2·6H2O and 0.8 mmol 2,6-naphthalenedicarboxylic acid dipotassium salt were dispersed in 100 ml of a mixed solution of anhydrous ethanol and deionized water (volume ratio 4:1), ultrasonically dispersed and magnetically stirred at room temperature to obtain a homogeneous first mixed solution; the first mixed solution was transferred to a high-pressure reactor and heated at 180℃ for 24 h to obtain Co-MOFs material. The obtained Co-MOFs material was conventionally vacuum dried at 80℃ for 12 hours (instead of freeze-drying), and then directly placed in a tube furnace and annealed at 700℃ for 2 hours under an argon atmosphere at a heating rate of 5℃ / min. After cooling to room temperature, a control sample was obtained.
[0107] The comparative sample was fabricated into a thin-film electrode using the same method as in Specific Example 1, and its electromagnetic shielding effectiveness was tested under the same conditions. The results showed that the electromagnetic shielding effectiveness of this comparative sample in the 8.2-12.4 GHz frequency range was significantly lower than that of the three-dimensional porous Co@C sponge in Specific Example 1 (54.3 dB). This indicates that the addition of alkali metal additives, the freeze-drying process, and the suitable pyrolysis temperature (400-600℃) have a synergistic effect, and all three factors jointly promote the improvement of the electromagnetic shielding performance of the three-dimensional porous carbon-based sponge.
[0108] This disclosure also provides a self-supporting porous carbon-based thin film, which is prepared according to a method for preparing a self-supporting porous carbon-based thin film as described in the embodiments of this disclosure.
[0109] This disclosure also provides an electromagnetic shielding material, including the three-dimensional self-assembled porous carbon-based electromagnetic shielding material described in the embodiments of this disclosure, or the self-supporting porous carbon-based thin film described in the embodiments of this disclosure.
[0110] This disclosure also provides an electronic device comprising the three-dimensional self-assembled porous carbon-based electromagnetic shielding material described in the embodiments of this disclosure, or comprising the self-supporting porous carbon-based thin film described in the embodiments of this disclosure.
[0111] This disclosure also provides a chip comprising the three-dimensional self-assembled porous carbon-based electromagnetic shielding material described in the embodiments of this disclosure, or comprising the self-supporting porous carbon-based thin film described in the embodiments of this disclosure.
[0112] This disclosure also provides an electronic device that includes the chip described in the embodiments of this disclosure.
[0113] According to the technical solution provided in this disclosure, efficient electromagnetic shielding is achieved by constructing a three-dimensional porous carbon-based sponge with synergistic effects of multi-level structural units and multi-level pores. This material uses two-dimensional nanosheets as the basic structural unit. Each nanosheet is a composite sheet structure, formed by a porous carbon framework connecting magnetic nanoparticles through in-situ self-assembly. The magnetic nanoparticles are embedded or anchored on the surface and interior of the carbon framework, resulting in a rough surface morphology for the nanosheets, exhibiting both dielectric and magnetic loss capabilities. Multiple two-dimensional nanosheets are further stacked and interleaved through self-assembly to form a macroscopic three-dimensional flower-like structure. This structure not only provides structural support but also creates numerous gaps between the nanosheets, forming macropores. Simultaneously, mesopores are distributed within and on the surface of the nanosheets, thus forming a multi-level porous structure with interconnected mesopores and macropores. In this multi-level pore structure, large pores are used to scatter and reflect incident electromagnetic waves multiple times to enhance scattering and reflection losses, while mesopores are used to extend the propagation path of electromagnetic waves to enhance ohmic and dielectric losses. The two types of pores work together to effectively overcome the problem that electromagnetic waves are difficult to penetrate into the interior of traditional carbon-based materials due to the skin effect and impedance mismatch. At the same time, multiple reflection losses and wide-band dielectric losses are achieved through the synergistic superposition of magnetic and dielectric losses, which significantly enhances the electromagnetic shielding effectiveness of the material.
[0114] The above description is merely a preferred embodiment of this disclosure and an explanation of the technical principles employed. Those skilled in the art should understand that the scope of the invention involved in this disclosure is not limited to technical solutions formed by specific combinations of the above-described technical features, but should also cover other technical solutions formed by arbitrary combinations of the above-described technical features or their equivalents without departing from the inventive concept. For example, technical solutions formed by substituting the above-described features with (but not limited to) technical features disclosed in this disclosure that have similar functions.
Claims
1. A three-dimensional self-assembled porous carbon-based electromagnetic shielding material, characterized in that, The three-dimensional self-assembled porous carbon-based electromagnetic shielding material comprises: a three-dimensional porous carbon-based sponge; wherein: The three-dimensional porous carbon-based sponge has a three-dimensional flower-like structure, which is formed by multiple two-dimensional nanosheets contained in the three-dimensional porous carbon-based sponge through self-assembly and interlacing. The surface of the two-dimensional nanosheet has a rough morphology and a composite sheet structure. The composite sheet structure is formed by the self-assembly of magnetic nanoparticles connected by a porous carbon skeleton. The magnetic nanoparticles are embedded or anchored to the surface and interior of the porous carbon skeleton. The three-dimensional porous carbon-based sponge contains a hierarchical pore structure, which is formed by interconnected mesopores and macropores. The gaps between the multiple two-dimensional nanosheets constitute the macropores, and the mesopores are distributed inside and on the surface of the two-dimensional nanosheets. The large aperture is used to scatter and reflect the incident electromagnetic wave multiple times to enhance scattering loss and reflection loss; the meso aperture is used to extend the propagation path of the incident electromagnetic wave to enhance ohmic loss and dielectric loss.
2. The three-dimensional self-assembled porous carbon-based electromagnetic shielding material according to claim 1, characterized in that, The three-dimensional porous carbon-based sponge is also doped with heteroatoms; the heteroatoms are covalently doped into the lattice interior and surface of the porous carbon framework.
3. The three-dimensional self-assembled porous carbon-based electromagnetic shielding material according to claim 2, characterized in that, in: The heteroatoms include non-metallic elements, including one or more of nitrogen, fluorine, phosphorus, and sulfur; the heteroatoms exist in the three-dimensional porous carbon-based sponge in the form of single-element doping or multiple-element co-doping.
4. The three-dimensional self-assembled porous carbon-based electromagnetic shielding material according to claim 2, characterized in that, The heteroatoms account for 1 wt% to 5 wt% of the mass of the three-dimensional porous carbon-based sponge.
5. The three-dimensional self-assembled porous carbon-based electromagnetic shielding material according to claim 1, characterized in that, The specific surface area of the three-dimensional porous carbon-based sponge is 400 m². 2 g -1 ~800 m 2 g -1 .
6. The three-dimensional self-assembled porous carbon-based electromagnetic shielding material according to claim 1, characterized in that, The magnetic nanoparticles include one or more of iron, cobalt, and nickel, and the particle size of the magnetic nanoparticles is 5 nm to 10 nm.
7. The three-dimensional self-assembled porous carbon-based electromagnetic shielding material according to claim 1, characterized in that, The diameter of the mesopores is in the range of 2 nm to 50 nm, the diameter of the macropores is in the range of 50 nm to 120 nm, the thickness of the two-dimensional nanosheets is 30 nm to 80 nm, and the aspect ratio is 20 to 100; the diameter of a single flower unit of the three-dimensional flower structure is 8 μm to 12 μm.
8. A method for preparing the three-dimensional self-assembled porous carbon-based electromagnetic shielding material according to any one of claims 1 to 7, characterized in that, The preparation method includes: Magnetic metal-based MOF materials are generated based on magnetic metal salts and organic ligands; Magnetic metal-based MOFs sponges are generated based on the aforementioned magnetic metal-based MOFs materials and alkali metal additives; The magnetic metal-based MOFs sponge was subjected to pyrolysis treatment to obtain a three-dimensional porous carbon-based sponge. The three-dimensional porous carbon-based sponge is contained within the three-dimensional self-assembled porous carbon-based electromagnetic shielding material.
9. The preparation method according to claim 8, characterized in that, The magnetic metal-based MOFs material generated based on magnetic metal salts and organic ligands includes: The magnetic metal salt and the organic ligand are dispersed in a solvent, ultrasonicated and stirred to obtain a homogeneous first mixed solution; the first mixed solution is then heated to obtain the magnetic metal-based MOF material. The process of generating magnetic metal-based MOF sponges based on the magnetic metal-based MOFs material and alkali metal additives includes: The magnetic metal-based MOFs material and the alkali metal additive are dispersed in a solvent to obtain a uniform second mixed solution; the second mixed solution is freeze-dried to obtain the magnetic metal-based MOFs sponge.
10. The preparation method according to claim 9, characterized in that, in, The solvent comprises anhydrous ethanol and deionized water; the volume ratio of anhydrous ethanol to deionized water is 3:1 to 5:1; the temperature range of the heating reaction is... The heating reaction lasts for 24 hours; the freeze-drying temperature range is... The freeze-drying time ranges from 30 h to 60 h.
11. The preparation method according to claim 9, characterized in that, The heating reaction of the first mixed solution includes: first transferring the first mixed solution to a polytetrafluoroethylene reaction flask and then heating the first mixed solution to react. The freeze-drying of the second mixed solution includes: first transferring the second mixed solution into a polytetrafluoroethylene reaction flask and then freeze-drying the second mixed solution.
12. The preparation method according to claim 8, characterized in that, The pyrolysis treatment includes: heating the magnetic metal-based MOF sponge to the annealing temperature under a protective atmosphere, annealing for a preset time, and then cooling to room temperature.
13. The preparation method according to claim 12, characterized in that, The protective atmosphere includes: an argon atmosphere; the annealing temperature is... Within the range, the preset annealing time is The heating rate is .
14. The preparation method according to claim 8, characterized in that, The mass ratio of the alkali metal additive to the magnetic metal-based MOF material is 2:1 to 4:
1.
15. The preparation method according to claim 8, characterized in that, The magnetic metal salt includes one or more of cobalt nitrate, iron nitrate, and nickel nitrate; the organic ligand includes dipotassium salt of 2,6-naphthalenedicarboxylate.
16. The preparation method according to claim 8, characterized in that, The alkali metal auxiliaries include one or more of the following: metal chlorides, metal sulfates, metal carbonates, and metal bicarbonates. The metal chlorides include sodium chloride and / or potassium chloride; the metal sulfates include sodium sulfate and / or potassium sulfate; the metal carbonates include sodium carbonate and / or potassium carbonate; and the metal bicarbonates include sodium bicarbonate and / or potassium bicarbonate.
17. The preparation method according to claim 8, characterized in that, Before pyrolyzing the magnetic metal-based MOFs sponge, the preparation method further includes: mixing the magnetic metal-based MOFs sponge with a heteroatom source to dope the three-dimensional porous carbon-based sponge with heteroatoms.
18. The preparation method according to claim 17, characterized in that, The pyrolysis treatment of the mixed materials includes: The mixed material is heated to the annealing temperature under a protective atmosphere, annealed for a preset time, and then cooled to room temperature to form a non-metallic doped three-dimensional porous carbon-based sponge.
19. The preparation method according to claim 18, characterized in that, The heteroatom source includes: a non-metallic dopant source; the non-metallic dopant source in the heteroatom source includes one or more of urea, ammonium fluoride, sodium hypophosphite, and sulfur; the mass ratio of the non-metallic dopant source to the magnetic metal-based MOF sponge is 10:1 to 20:1; the protective atmosphere includes: an argon atmosphere; the annealing temperature is... The preset annealing time is The heating rate is .
20. A method for preparing a self-supporting porous carbon-based thin film, characterized in that, The preparation method includes: The three-dimensional self-assembled porous carbon-based electromagnetic shielding material according to any one of claims 1 to 7 is dispersed in water with a polymer adhesive at a preset mass ratio to obtain a mixed slurry. The mixed slurry is vacuum filtered to form a thin film, and the film is dried to obtain a self-supporting porous carbon-based thin film.
21. The preparation method according to claim 20, characterized in that, in: The polymer adhesive includes: polyvinyl alcohol; The preset mass ratio is ; The drying process is constant-temperature vacuum drying, with a drying temperature of [temperature value missing]. The drying time is ; The thickness of the self-supporting porous carbon-based thin film is .
22. The preparation method according to claim 20, characterized in that, in: The drying temperature includes: The drying time includes: .
23. A self-supporting porous carbon-based thin film, characterized in that, The self-supporting porous carbon-based thin film is prepared by the preparation method according to any one of claims 20 to 22.
24. An electromagnetic shielding material, characterized in that, It includes the three-dimensional self-assembled porous carbon-based electromagnetic shielding material according to any one of claims 1 to 7, or the self-supporting porous carbon-based thin film according to claim 23.
25. An electronic device, characterized in that, It includes the three-dimensional self-assembled porous carbon-based electromagnetic shielding material according to any one of claims 1 to 7, or the self-supporting porous carbon-based thin film according to claim 23.
26. A chip, characterized in that, It includes the three-dimensional self-assembled porous carbon-based electromagnetic shielding material according to any one of claims 1 to 7, or the self-supporting porous carbon-based thin film according to claim 23.
27. An electronic device, characterized in that, Includes the chip described in claim 26.